Identification of Novel Thermosensors in Gram-Positive Pathogens - Fernández, Pilar; Díaz, Alejandra Raquel; Ré, María Florencia; Porrini, Lucía; de Mendoza, Diego; Albanesi, Daniela; Mansilla, María Cecilia (Frontiers in Molecular Biosciences, 2020)
Temperature is a crucial variable that every living organism, from bacteria to humans, need to sense and respond to in order to adapt and survive. In particular, pathogenic bacteria exploit host-temperature sensing as a cue for triggering virulence gene expression. Here, we have identified and characterized two integral membrane thermosensor histidine kinases from Gram-positive pathogens that exhibit high similarity to DesK, the extensively characterized cold sensor histidine kinase from Bacillus subtilis. Through in vivo experiments, we demonstrate that SA1313 from Staphylococcus aureus and BA5598 from B. anthracis, which likely control the expression of putative ABC transporters, are regulated by environmental temperature. We show here that these histidine kinases can phosphorylate the non-cognate response regulator DesR, partner of DesK, both in vitro and in vivo, inducing in B. subtilis the expression of the des gene upon a cold shock. In addition, we report the characterization of another DesK homologue from B. subtilis, YvfT, also closely associated to an ABC transporter. Although YvfT phosphorylates DesR in vitro, this sensor kinase can only induce des expression in B. subtilis when overexpressed together with its cognate response regulator YvfU. This finding evidences a physiological mechanism to avoid cross talk with DesK after a temperature downshift. Finally, we present data suggesting that the histidine kinases studied in this work appear to monitor different ranges of membrane lipid properties variations to mount adaptive responses upon cooling. Overall, our findings point out that bacteria have evolved sophisticated mechanisms to assure specificity in the response to environmental stimuli. These findings pave the way to understand thermosensing mediated by membrane proteins that could have important roles upon host invasion by bacterial pathogens.